Strategi Pemasaran Berbasis Digital Dalam Upaya Peningkatan Penjualan Berprinsip Syariah Islam - Fatkhur Rohman Albanjari; Nugraheni Fitroh Rezqi Syakarna (xxxx-xxxx, 2022)
This research is motivated by the development of technology and small industries in the fashion world, especially knitting among women in Karanganyar village, Pule district, Trenggalek which is getting better, the majority of women there are housewives and farmers so that in between their time they launch a knitting business as a hoi and income. The purpose of the study is to analyze the application of digital-based marketing strategies in increasing sales with Islamic sharia principles.the research method used is a descriptive type qualitative with data collection techniques using interviews, observations and documentation. Data analysis uses three stages, namely data reduction, data presentation, and conclusions, as well as data validity using trianggulation. The results showed that the products traded were halal and tayib, in a place to use social media to reach the widest market, sales promotion was carried out honestly and openly, prices determined were in accordance with quality and did not damage market prices, competition was carried out in a healthy and Islamic manner and the distribution of goods was carried out with great Mandate.